Senator Sarah Hanson-Young Calling Out the Slut Shamers - Shania Sukma Patrianegari Mulyono; Lina Purwaning Hartanti (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
This study analyzes the use of illocutionary types of BBC Youtube channel 'You're not fit to call yourself men,' Sarah Hanson-Young tells senators, where Senator Sarah Hanson-Young was being slut shamed by other members of the parliament. This study uses the descriptive qualitative method. The objectives of this study are to find the illocutionary acts used in the speech and also to figure out how the speaker uses self-disclosure to engage the audience. Documentation technique was used to collect the data, and the data were then analyzed by using Searle's theory to analyze the use of illocutionary acts, and Jourard's and M Leary's to analyze the use of self-disclosure to engage the audience. The results of this study showed that 2 illocutionary acts were equally dominant in the speech which was assertive and expressive. In addition, Declaratives were less dominant, and the two other types, directives and commissives, were not found in the speech. This study also found that The speaker’s use of expressives illocutionary acts to perform her self-disclosure was a successful technique to engage other members of parliament.